The verticalization of teaching at the Federal Institute of Mato Grosso (Research, Society and Development, 2020)
With roots dating back to the early twentieth century, the Federal Network of Vocational and Technological Education (RFEPCT) has, throughout its history, undergone several social, historical and educational transformations, triggering significant changes in the way of thinking policies in the area of education. The Federal Institutes born from the year 2008 through Law 11.892 / 2008 is an integral part of this network and represent the newest materialization of public policies aimed at professional education in Brazil. Verticalization is one of the characteristics of these educational institutions, and aims, according to their founding law, to optimize the physical infrastructure, staffing and management resources, as well as to integrate basic and higher education. Due to the importance that the verticalization process has assumed in this new configuration of the Federal Network, this study was developed. As for the objectives it was characterized as an exploratory research, since it was sought an understanding of the concept of verticalization and how it has been occurring within the Federal Institute of Mato Grosso (IFMT). The procedures of bibliographic and documentary research were adopted. To understand this vertical context, we proceeded with an analysis of the information extracted from IFMT normative documents, and making a counterpoint to the courses offered, which characterize the vertical in this institution. From the work done it was found that in the scope of IFMT is present in both its documents and the offer of courses, reflecting the intention of the network to have it as its objective.